Effect of Root Culturing and Fertilizers on Morphology and Outplanting Survival of Ulmus villosa Seedlings - Chauhan, Sanjeev K.; Sharma, G. K.; Singh, Charan (Indian Forester, 2008)
Seedlings on raised beds were subjected to a variety of root culturing and fertilizer treatments. Seedlings parameters were recorded at the time of outplanting. The undercutting and wrenching treatments produced shorter and thin stemmed seedlings with reduced shoot, seedling and total root dry weight in comparison to the untreated seedlings. The number, length and dry weight of lateral roots were stimulated in treated seedlings. The application of N and P fertilizers individually and in conjunction with undercutting and wrenching also showed significant improvement in growth and biomass characters. The application of 80 kg N/ha and 30 kg P2O5/ha were considered appropriate for better performance of seedlings. The seedlings were better conditioned to withstand outplanting stress and showed improved survival over the respective control.